Carboxymethylation of kappa-carrageenan for intestinal-targeted delivery of bioactive macromolecules - Leong, K.H.; Chung, L.Y.; Noordin, M.I.; Mohamad, K.; Nishikawa, M.; Onuki, Y.; Morishita, M.; Takayama, K. (2011)
The work presented herein discusses the carboxymethylation of kappa-carrageenan, a natural linear polysaccharide, to afford a pH-dependent swelling property allowing for intestinal-targeted delivery of bioactive macromolecules. The carboxymethylation conditions with respect to the volume and concentration of sodium hydroxide (V(NaOH), C(NaOH)), weight of monochloroacetic acid (W(MCA)), and reaction temperature (T) were optimized using a response surface method incorporating a multivariate spline interpolation technique (RSM(s)). Fluorescein isothiocyanate-labeled dextran (FD-4; 4.4 kDa) was used as a hydrophilic macromolecule model. Beads made from encapsulating FD-4 in the carboxymethylated kappa-carrageenan displayed pH-dependent swelling and encapsulation efficiency of 74. The release of FD-4 was low (23 +/- 2) in simulated gastric fluid (SGF) and high (90 +/- 3) in simulated intestinal fluid in a 2 h dissolution study. An additional lambda-carrageenan coating on the surface of the beads further reduced the FD-4 release in SGF. These carboxymethylated kappa-carrageenan beads may provide an efficient alternative approach for the oral delivery of hydrophilic macromolecules to the intestinal tract. (C) 2010 Elsevier Ltd. All rights reserved.